2001
DOI: 10.1093/ndt/16.4.824
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplantation in the elderly: a long‐term, single‐centre experience

Abstract: Renal transplantation should be considered in patients older than 60 years, since graft survival is excellent in this population. Although these patients have a shorter life expectancy, they benefit from renal transplantation similarly to younger kidney transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
21
0
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 15 publications
8
21
0
11
Order By: Relevance
“…Donor age had little influence on graft survival in the older recipient group and no influence on patient survival. We conclude, like others, 11 that donor age is less important in elderly patients: the potentially short graft survival does not affect patient survival.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Donor age had little influence on graft survival in the older recipient group and no influence on patient survival. We conclude, like others, 11 that donor age is less important in elderly patients: the potentially short graft survival does not affect patient survival.…”
Section: Discussionsupporting
confidence: 82%
“…11 There are, however, some reports where aged recipients had a rejection rate higher than younger controls, ranging from 40% to 70%. 13,14 This can be partially explained, in these studies, by worse compatibility in terms of HLA mismatches presented by the elderly subset of patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…12 Some authors have argued that the better results reported in some series of older recipients may be due to less acute rejection in elderly recipients. 7,13 Consistent with these observations, we also found a significantly lower rejection rate among the older group, which may also contribute to the survival results.…”
Section: Discussionsupporting
confidence: 88%
“…Wolfe et al [29] compared the survival of primary deceased donor transplant recipients with other dialysis patients and found that among renal transplant recipients patients aged 60-74 years, the cumulative survival rate improved after the first year post-transplantation. More recent studies indicate that in elderly ESRD patients, survival at 1, 5, and 10 years is approximately 80% to 90%, 70%, and 50% respectively [38][39][40][41][42][43][44][45][46]. In the United States there are currently over 16,000 ESRD patients older than 65 years waiting for a kidney transplantation, representing 18% of all listed candidates [1].…”
mentioning
confidence: 99%